ANALISIS KARAKTERISTIK SOSIAL EKONOMI PENYULUH DENGAN PELAKSANAAN PENYULUHAN DI KABUPATEN MINAHASA - Mangare, Gabriella; Sondakh, B F.J; Oley, F S; Massie, M T (Universitas Sam Ratulangi, 2016)
ANALYSIS OF SOCIO-ECONOMIC CHARACTERISTICS OF EDUCATOR WITH EXTENSION IN THE DISTRICT MINAHASA. Extension workers has a strategic role in improving the welfare of farmers / ranchers. One of the factors that influence the success of the extension duties is the state socio-economic background or socio-economic characteristics of each extension. However, the extent of the relationship between socioeconomic characteristics with the implementation of the extension in Minahasa unknown. Based on these problems, the purpose of this study was to determine the relationship of these characteristics with the execution of tasks with good extension. This study uses survey data collection on respondents extension and analyzed descriptively. The collected data are presented in tables cross between variables (education and experience) were observed and analyzed by looking at the distribution Trends. The results showed that the factor of higher education Bachelor (S1) tend to be better than not on the Bachelor in execution of duty. On the other hand experience of long-serving and who have served a long time showed relatively recent trend duty (< 20 years) is better than the longtime (> 20 years). As a conclusion that the social and economic characteristics based on the educational background related to the implementation of the tasks. The higher the education the better performance of its duties educator. Â Keywords: Characteristics , Social Economy, Duties , Extension